PERKEMBANGAN BATERAI DAN CHARGER UNTUK MENDUKUNG PEMASYARAKATAN SEPEDA LISTRIK DI INDONESIA - N. M. A. Wijaya; I. N. S. Kumara; Y. Divayana (Jurnal SPEKTRUM, 2021)
Nowadays electric vehicles begin to grow and are supported by improved batterytechnology such as smaller size and capable of storing large amounts of energy. One type ofsimple electric vehicle is an electric bicycle. This paper reviews the availability of batteries andbattery chargers for electric bicycles in Indonesia. The review includes a discussion on thetechnical specifications, manufacturer, the vendor of the battery, and battery charger. Thesurvey produced a data consists of 117 batteries and 54 chargers and then processed to obtainstatus on the availability in the domestic market. The information regarding the availability ofbatteries and battery chargers for electric bicycles is expected to be used as a quick referencefor the community in choosing batteries and battery chargers for electric bicycles and canprovide an overview to stakeholders about the status of batteries and chargers in conductingresearch and development of batteries and charging equipment for electric vehicles.